2021
DOI: 10.1177/15248380211029404
|View full text |Cite
|
Sign up to set email alerts
|

Processes of Multiprofessional Child Protection Decision Making in Hospital Settings: Systematic Narrative Review

Abstract: The aim of this systematic narrative literature review is to explore empirical evidence as to how a multiprofessional approach to child protection decision making is implemented in hospitals settings. Child protection cases where there is a suspicious serious injury suspected sexual abuse or serious neglect are often investigated in hospital, involving a number of relevant professions. Five electronic bibliographic databases were used for the search. To be included in the review studies had to be published in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Physicians who have access to expert consultation report feeling more secure in their decisions [ 30 , 32 ], which may be even more important for less experienced learners. A recent and compelling review by Alfandari and Taylor [ 81 ] offers important information about the state of the evidence regarding the implementation of multi-professional child protection decision-making teams in hospital-based settings, including their effectiveness, structure, and processes. Across the 26 studies from 10 different countries, the authors reported significant variability in team composition, role structure, and decision-making procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physicians who have access to expert consultation report feeling more secure in their decisions [ 30 , 32 ], which may be even more important for less experienced learners. A recent and compelling review by Alfandari and Taylor [ 81 ] offers important information about the state of the evidence regarding the implementation of multi-professional child protection decision-making teams in hospital-based settings, including their effectiveness, structure, and processes. Across the 26 studies from 10 different countries, the authors reported significant variability in team composition, role structure, and decision-making procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Across the 26 studies from 10 different countries, the authors reported significant variability in team composition, role structure, and decision-making procedures. In addition, evaluations of team-based decision-making models have centred on CM identification, with no available data on the impacts of team-based decision making on the outcomes for children who have experienced CM and their families; this is an important area for future research [ 81 ]. Despite this, the authors offer important recommendations with respect to the need to honour teamwork as a “stand-alone skill that is acquired through education, training, and experience” (p. 15), and which can be fostered using low-stakes pedagogical approaches, such as case-based learning, prior to direct clinical encounters.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the approach to IV in health by the United Nations and the World Health Organization, it is important to note that it has been discussed to a limited extent in such agendas, which further limits the mobilization of resources in actions related to monitoring and its coping. In addition to that, most of the studies related to child protection in health services proposed by several countries have focused on identifying and acting on the notification of cases of violence that reach such institutions; however, it appears that there is still a large gap in studies on violence in or by health services (5,(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…A review of the existing literature on HCPs' recognition and response to child maltreatment shows that most studies were carried out in hospital‐based services and Western countries that implement mandatory reporting laws, such as the United States, Australia, and Canada (Alfandari & Taylor, 2021a; Enosh et al, 2020; Gilbert et al, 2009; Mathews & Kenny, 2008; McTavish et al, 2017). In this section we argue that the preoccupation with practice experience in hospital settings bounded by mandatory reporting legislations, generates evidenced‐based knowledge that is skewed toward serious incidents of CAN, reporting practices, and HCPs' fidelity with rules and guidelines and which is insufficient to help HCPs working in community health care services make better decisions.…”
Section: Going Beyond Available Evidence‐based Knowledgementioning
confidence: 99%
“…Together with the weight given in research and practice to establishing collaborative multi‐professional approaches to child protection decision making as a mean to promote children's safety and well‐being (Alfandari, 2019; Alfandari & Taylor, 2021a, 2021b), a more nuanced analysis of important variations in judgement making across professional groups is still required (Eisikovits et al, 2015; Svärd, 2017). For example, studies on multi‐professional child protection decision making by professionals representing different systems, e.g., child protection, mental health, and courts, indicated critical variations exist between professions in perceptions of thresholds for substantial harm and referrals to universal services or child protection interventions (Alfandari & Taylor, 2021b; Gilbert et al, 2009; Hood et al, 2017; Rouf et al, 2012).…”
mentioning
confidence: 99%